Objective Reality - Vinciūnas, Juozas Vytautas (Problemos, 1974)
The ontological conception of matter is critically discussed in the paper. The author points out that the content of matter as of a philosophical category can be disclosed only by making clear its relation to consciousness for it is only in this case that it acquires its content; the instrumental character of the concept of matter is underlined. The existence and its criterion problems are discussed against the background of the dialectic-materialistic and positivistic methodologies set opposite. In studying matter physics is not any more competent than other sciences; attempts to view mass as a measure of the quantity of matter are criticized.